Role of TDP2 in the repair of DNA damage induced by the radiomimetic drug Bleomycin - Naoto Shimizu; Kazuki Izawa; Mubasshir Washif; Ryosuke Morozumi; Kouji Hirota; Masataka Tsuda (Genes and Environment)
Abstract Background Bleomycin (Bleo) is a glycopeptide with potent antitumor activity that induces DNA double-strand breaks (DSBs) through free radical generation, similar to ionizing radiation (IR). Therefore, Bleo is considered a radiomimetic drug. However, differences in DNA repair mechanisms between IR- and Bleo-induced DNA damage have not been fully elucidated. Therefore, in the present study, we examined a panel of repair-deficient human TK6 cell lines to elucidate the relative contributions of individual repair factors. Results Our comprehensive profiling indicated that both non-homologous end joining (NHEJ) and homologous recombination (HR) contributed to DSB repair induced by X-rays and Bleo. Furthermore, tyrosyl-DNA phosphodiesterase (TDP)-related repair was a significant factor for cellular sensitivity to Bleo treatment. TDP1 −/− /TDP2 −/− cells exhibited greater sensitivity to Bleo than TDP1 −/− or TDP2 −/− cells, but not to X-rays. In addition, we determined whether TDP2 is involved in the repair of Bleo-induced DSBs using a neutral comet assay. In TDP1-deficient cells, knockout of TDP2 resulted in a significant delay in the repair kinetics of DSBs induced by Bleo, but not by X-rays. Conclusions The contribution of the TDP-related pathway to DSB repair significantly differed between IR and radiomimetic drugs. The discovery of this novel TDP2-dependent repair of DSBs resulting from radiomimetic drug exposure indicates that TDP1 and TDP2 inhibition in combination with radiomimetic drugs represents a strategy for cancer treatment.